Tobacco Use Among People Incarcerated in Western Europe: A Systematic Review and Meta-analysis - Damilola Sophia Alokan; Zubair Kabir (SAGE Publishing, 2022)
Background Evidence suggests that the prevalence of tobacco use has declined significantly in the general population but still remains high among people incarcerated in high-income countries. Tobacco use is the second leading risk factor of mortality and morbidity worldwide. The objective of this study is to synthesize evidence on the prevalence of smoking among people incarcerated in Western European countries. Methods We searched the PubMed database for articles published between June 2010 and June 2020, website of international organizations and hand-searching references. One author reviewed studies that met pre-defined inclusion criteria, and this was cross-validated by a second reviewer, following the MOOSE guidelines. The Meta prop command of Stata (V16) was used for pooling smoking prevalence estimates. Random effects modelling, heterogeneity with subgroup analysis and publication bias was assessed. Results Out the 236 identified articles, 25 with full texts were eligible, and 16 were finally included in this study. The overall pooled estimate of smoking prevalence was 72.3%, 95% CI (54.8-84.7), and high heterogeneity (I2 = 99.73%). Females had a pooled prevalence 44.1% (95% CI 9.4-82.6) while males 83.3% (95% CI 72.0-92.1). The total number of prisoners combined in this study was 16,435 (ranging from 31-21,451) with age ranging from 24-43 years. Conclusion A relatively high smoking rate was observed among incarcerated people - higher among the male population. The study findings are useful for informing policy-makers of the existing burden of smoking in special vulnerable populations across Western Europe-and the need for comprehensive tobacco control policies in different population settings.